Mostras de Sentido no Fluir do Tempo: Estudos de Humanismo e Renascimento - Nair de Nazaré Castro Soares (Humanitas Suplemmentum, 2020)
This volume brings together a series of articles on the Classical Tradition, Humanism and the Renaissance that stand for the scientific work developed by the author throughout her activity as a researcher and Full Professor of the Faculty of Arts and Humanities of the University of Coimbra. This edition was organized on the occasion of the end of her teaching career, and is divided into two major themes - Theatre, and History of Ideas. Each article follows the bibliographical references of the publication in which it was previously edited.